KONSEP HUKUM ISLAM DALAM MEWUJUDKAN STABILITAS DAN PERUBAHAN DALAM MASYARAKAT - Bahar, Sunuwati; Saudi; Luthfiah; Kurniati; Musyahid, Achmad (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2023)
Sharia is a system of laws which has been in force for millennia, whereas jurisprudence specifies the specific formulation of Islamic law to be implemented on an individual case at a particular place and time. Both are distinguishable, but they're inseparable. In order to avoid confusion as to the meaning of Islamic law, It is suggested that the meaning of Islamic law itself be renewed either as a result of teaching or as a consequence of interpretation, interpretation, or thought of the mujtahids. In this study, qualitative descriptive was used. Interviews, observation, and documentation were used to gather data. Data gathering, data reduction, data presentation, and data conclusions are all used in this study's data analysis methodologies. The findings demonstrated that, if Islamic law has grown to be regarded as necessary for a society to maintain its stability, alterations to the law may result in social transformation. Islamic law's goal and essence are reflected in the notion of legal transformation it has brought about.